Soil properties and silage quality in response to oat and pea seeding ratios and harvest stage on the Qinghai-Tibetan Plateau - Liu, Wen; Zhao, Liansheng; Chen, Yakun; Shen, Yifan; Luo, Zhijie; Chen, Yanbin; Evans, Alexander C. O.; Bu, Dengpan (Frontiers in Sustainable Food Systems, 2023)
Livestock intensification improves production efficiency and increases the demand for quality forages to feed ruminants. Novel combinations of forage plants, particularly Gramineae and Leguminous plants, are considered feasible combinations. This study explored an oat-pea mixed seeding strategy as an approach to improving silage quality on the Qinghai-Tibetan Plateau. Before ensiling, lactic acid bacteria were added to forage of five different mixed seeding proportions of oats (O) and peas (P) (oats:peas O10:P0, O8:P2, O7:P3, O5:P5, O0:P10) at two harvesting periods (the early flowering stage and the milk ripening stage for oats). Mixed seeding changed the soil quality parameters and the O5P5 group showed the lowest pH values and highest LA contents. Furthermore, the O5P5 group increased the number of tillers/branches and produced silage with the highest CP content. In conclusion, this study found that the selection of oat-pea mixed seeding as O5P5 and harvesting at the milk ripening stage of oats is recommended as a desirable oat-pea mixed seeding strategy for producing high quality silage.